Crystalline Phase, Microstructure, Optical Properties and Electrical Resistivity in Monovalent Doped Pr0.75Na0.2Ag0.05Mn1-xCoxO3 (x = 0 - 0.05) Manganites - Azizi, Amer (Enhanced Knowledge in Sciences and Technology, 2024)
Monovalent doped Pr0.75Na0.2Ag0.05Mn1-xCoxO3 (x = 0.00, 0.02, and 0.05) have been studied to investigate the effect of crystalline phase, microstructure, and optical properties as well as electrical resistivity using X-ray diffraction (XRD), scanning electron microscope (SEM), Fourier-transform infrared spectroscopy (FTIR) and four-point probe respectively. Study on reporting the effect elemental substitution of Co-doped on monovalent perovskite manganites in crystalline phase, microstructure, optical properties, and electrical studies are still not extensively investigated. All samples were prepared using solid state reaction methods which involved a few processes such as mixing and grinding high purity powders, calcinations, pelleting, and sintering. XRD result showed all samples have been analysis as an orthorhombic structure with Pnma space group and the lattice parameter as well as the unit cell volume was observed to be continually decreased with Co content which can be suggest due to the factor of size mismatch between the Co3+ ions and Mn3+ ions. The morphological study shows the reduction in grain size in the Co-doped manganite samples which indicates that that increasement of Co doping can promote growth of grain size and agglomeration. FTIR spectra indicated a shift in the vibration stretching mode towards higher wavenumbers for all samples which can be attributable to the reduction in lattice parameter. The results from the four-point probe analysis showcased a decrease in resistivity with an increasing concentration of Co-doping, suggesting heightened charge carrier density and conductivity and providing insights into the electrical properties. As for that, the effect of Co3+ ions doped on Pr0.75Na0.2Ag0.05MnO3 shows a significant result on influencing the crystalline phase, microstructure, optical properties, and electrical resistivity.